Contrasted land use and development trajectories in the Brazilian Amazon - Mertens, B.; Piketty, M.G.; Venturieri, A.; Alves, D.; Tourrand, Jean François (2004)
The Amazon is the largest tropical forest area on Earth, and is undergoing rapid deforestation since the last four decades. These conversions are mostly located in frontier areas distributed along the so-called “arc of deforestation”. Within this large zone, various land use change processes are interacting through several modes of land valorization and organization. From two case studies in the state of Para (Brazil), the current paper aims at analyzing how these landscape dynamics in contrasted frontier areas are related to infrastructure development, ecological conditions, land tenure and fiscal policies, and to the evolution and the organization of the production, consumption and marketing chains of livestock products. The main objectives are to illustrate the spatial and temporal variability regarding incentives and disincentives to convert tropical forests for other agricultural uses and how do contrasted biophysical and socio-economic conditions (such as accessibility or land tenure) affect current and future land use and development trajectories, with a particular emphasis on the role of roads infrastructure. This study draws on complementary datasets, socio-economic census, key informants interviews and satellite remote sensing imagery, linked with geo-referenced information on human and biophysical conditions. These data were integrated in a GIS, and the analyses were supported quantitatively by using spatial econometric modelling approaches and landscape ecology tools.